(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
This article is devoted to the study of verbal presentations of emotional state of fear in a prose text; it reveals the elements of functional-semantic microfield of Fear, their division into thematic groups and synonymous rows. Moreover nominative units it has been analyzed the non-verbal elements of the emotional code.